Effectiveness of Planned Teaching Program on Knowledge Regarding Effects of Alcoholism among Adults - Sah, Indu; Dangol, SM (Journal of Gandaki Medical College-Nepal, 2018)
Background: Alcoholism is chronic progressive and often fatal disease. It is a primary disorder and not a symptom of other disease or emotional problems. The chemistry of alcohol allows it to effect nearly every type of cell in the body, including those in the central nervous system.Objectives: The main objectives of this study are 1) to assess the level of knowledge regarding effects of alcohol among rural adults, 2) to assess the post test knowledge regarding effects of alcohol among rural adults, and 3) to evaluate the effectiveness of planned teaching program on knowledge regarding effects of alcoholism.Methods: A Quasi-experimental one group pre-test post-test research design was adopted for the present study. The structured interview schedule was developed to collect data. The study was conducted at Challaghatta Village, Bangalore, Karnataka State, India and the data collected was analyzed and interpreted based on descriptive and inferential statistics.Results: The assessment of knowledge level of adults regarding effects of alcoholism revealed that the mean pretest was 9.6 with SD 3.06. Mean post-test was 20.04 with SD 1.6 and enhancement mean score 10.8 with SD 1.08 and paired t value 9 which shows statistically significant at p >0.05 level.Conclusion: The present study attempted to assess the effectiveness of planned teaching program (PTP) on knowledge of rural adults regarding effects of alcoholism and found that the developed PTP was effective in improving the knowledge of rural adults regarding effects of alcoholism.